Management of frenectomy on the superior labial frenulum with conventional technique: Management of frenectomy on the superior labial frenulum with conventional technique - Firman Salam; Hasanuddin Thahir; Febrianty (Makassar Dental Journal PDGI Makassar, 2024)
This case report describes the frenectomy procedure on the maxillary labial frenulum and its effect on the success of diastema closure orthodontic treatment. A 21-year-old male presented to the Periodontia Department of Hasanuddin University Dental and Oral Teaching Hospital for frenectomy. The patient complained of superior labial frenulum extending to palatine, diastema centralis, and was referred for frenectomy with conventional technique. The conventional technique involved engaging the fre-nulum using a hemostat inserted into the vestibule, and incisions were placed on the upper and lower surfaces of the hemostat followed by suturing the wound and closing it with a periodontal pack. It was concluded that frenectomy using the conventional technique was effective in closing the maxillary central diastema.